1985
DOI: 10.1111/j.1365-2044.1985.tb11052.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of tracheal tubes 3.0 and 3.5 mm internal diameter

Abstract: SummaryThe resistance of RAE, Riisch, Mallinckrodt paediatric and Portex plain nasal and oral tracheal tubes with internal diameters 3.0 mm and 3.5 mm was calculated at air flows of 1 to 10 litres per minute. Theflow resistance profiles of RAE and Rusch tracheal tubes was generally higher than those of Mallinckrodt paediatric and Portex plain tubes. All RAE and Riisch nasotracheal tubes of size 3.0 mm internal diameter and orotracheal tubes 3.0 mm internal diameter had aflow resistance exceeding 3.0 kPa litres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It became common to ‘down‐size’ the tube by approximately half a size. This reduction in internal diameter may decrease the likelihood of mucosal damage but results in a relatively large increase in resistance (due to the Hagen–Poiseuille equation), and a subsequent increased work of breathing during spontaneous breathing . However, there are few occasions when a child should be allowed to breathe spontaneously through a tracheal tube for any length of time; most commonly, this would occur at the end of a procedure shortly before tracheal extubation and so the increased resistance is not of real clinical concern.…”
Section: Advantages Of Cuffed and Uncuffed Tracheal Tubesmentioning
confidence: 99%
“…It became common to ‘down‐size’ the tube by approximately half a size. This reduction in internal diameter may decrease the likelihood of mucosal damage but results in a relatively large increase in resistance (due to the Hagen–Poiseuille equation), and a subsequent increased work of breathing during spontaneous breathing . However, there are few occasions when a child should be allowed to breathe spontaneously through a tracheal tube for any length of time; most commonly, this would occur at the end of a procedure shortly before tracheal extubation and so the increased resistance is not of real clinical concern.…”
Section: Advantages Of Cuffed and Uncuffed Tracheal Tubesmentioning
confidence: 99%
“…It became common to 'down-size' the tube by approximately half a size. This reduction in internal diameter may decrease the likelihood of mucosal damage but results in a relatively large increase in resistance (due to the Hagen-Poiseuille equation), and a subsequent increased work of breathing during spontaneous breathing [12]. However, there are few occasions when a child should be allowed to breathe spontaneously through a tracheal tube for any length of time; most commonly, this would occur at the end of a procedure shortly before tracheal extubation and so the increased resistance is not of real clinical concern.…”
Section: Gupta a Fraud And Misconduct In Clini-mentioning
confidence: 99%
“…In in vitro studies, ETTs of different brands have been reported to have caused different airway resistance levels, and extending ETTs with connectors have also been reported to have increased tube resistance (2,3). ETT closed system suctions (CSS) have their own connectors.…”
Section: Introductionmentioning
confidence: 99%